2016
DOI: 10.1055/s-0042-116590
|View full text |Cite
|
Sign up to set email alerts
|

Tabakkonsum und Inanspruchnahme medizinischer Leistungen im Jugendalter – Eine Analyse der KIGGS Daten

Abstract: In Germany, there is a lack of information on the correlation between tobacco use by adolescents and their utilization of medical care. The aim of this article is to identify possible early consequences of adolescent smoking. We conducted a re-analysis of cross-sectional data of the baseline wave (2003-2006) of the German Health Survey for Children and Adolescents (KiGGS). To examine the association between current smoking status and utilization of medical care during the 12 months before the interview, preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Our findings are consistent with previous studies in other countries, such as the USA ( 19 ), Canada ( 21 ), Spain ( 22 ), Switzerland ( 30 ), Denmark ( 31 ), Germany ( 32 ), South Korea ( 33 ) and the Middle East ( 34 ). Furthermore, a recent cohort study from Hubei Province in China suggested that smoking behaviors, such as quitting smoking early and consuming a small amount of cigarettes, would decrease health care utilization and medical costs ( 10 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are consistent with previous studies in other countries, such as the USA ( 19 ), Canada ( 21 ), Spain ( 22 ), Switzerland ( 30 ), Denmark ( 31 ), Germany ( 32 ), South Korea ( 33 ) and the Middle East ( 34 ). Furthermore, a recent cohort study from Hubei Province in China suggested that smoking behaviors, such as quitting smoking early and consuming a small amount of cigarettes, would decrease health care utilization and medical costs ( 10 ).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, a recent cohort study from Hubei Province in China suggested that smoking behaviors, such as quitting smoking early and consuming a small amount of cigarettes, would decrease health care utilization and medical costs ( 10 ). Apart from hospital admission and the number of hospital visits, research from Hvidtfeldt et al ( 31 ) and Fassmer et al ( 32 ) found that smokers had longer duration stays in the hospital than those who never smoked, which supports the conclusion that smoking elevates health care utilization.…”
Section: Discussionmentioning
confidence: 87%
“…In order to overcome the inconclusive results with respect to inequalities in HCSU and to follow the obstacles of differences in different needs and barriers with respect to health care among migrants and non-migrants in Germany, a study with a large nationally representative sample of persons with and without migration background is needed in order to be able to make a generally valid statement about the health care situation of migrants in Germany. However, earlier studies on the utilization of doctors and hospitalization of persons with and without migration background in Germany were based on regional samples [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ], samples of children and adolescents or elderly [ 16 , 22 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], samples of women [ 18 , 19 , 20 , 21 , 24 , 25 , 26 , 27 ], or only samples on specific medical conditions [ 5 , 29 , 34 , 36 , 37 ]. Merely a study from 2011 by Glaesmer et al [ 12 ] used a representative population survey of persons with direct and indirect migration background as well as those without to investigate differences in HCSU in Germany.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the above literature review, although some researchers examined the impact of smoking on health care utilization, there is limited evidence in developing countries, especially China (Rice et al, 1986;Wagner et al, 1995;Artalejo et al, 2000;Robbins et al, 2000;Izumi et al, 2001;Kahende et al, 2009;Woodruff et al, 2010;Levine et al, 2012;Lin et al, 2012;Azagba et al, 2013;Warner et al, 2013;Wacker et al, 2013;Khokhawalla et al, 2015;Keto et al, 2016;Fassmer et al, 2016). Additionally, there are few researchers using the longitudinal data set and estimating by a fixed or random effect logistic model in empirical study.…”
Section: Benefits Of Researchmentioning
confidence: 99%
“…In other developed countries and regions, Artalejo et al (2000) found that male smokers were hospitalized more frequently and made greater use of hospital emergencies compared with never smokers in Spain; Izumi et al (2001) indicated that the increased use of inpatient service among smokers, especially in males in Japan; Levine et al (2012) showed that current smokers were significantly related to increased health care utilization in Israel; Lin et al (2012) discovered that the addictive behavior of smoking was significantly associated with both outpatient and inpatient utilization in Taiwan; Azagba et al (2013) found that smokers consumed more hospitalization than never smoker, and former smokers who recently quit smoking used more health care services in Canada; Wacker et al (2013) presented that current and former smokers had a positive relationship with the health care utilization in Germany; Keto et al (2016) showed that middle-aged smokers visited primary health care professional more often per year than never smokers in Finland. Fassmer et al (2016) displayed that tobacco use was related to a greater utilization of medical care among adolescents in Germany.…”
Section: Tobacco Use and Health Care Utilizationmentioning
confidence: 99%